Circulating cell free DNA testing: are some test failures informative?. (8th January 2015) - Palomaki, G. E.; Kloza, E. M.; Lambert‐Messerlian, G. M.; van den Boom, D.; Ehrich, M.; Deciu, C.; Bombard, A. T.; Haddow, J. E.
Abstract Objective The proportion of circulating cell free DNA derived from the feto‐placental unit (fetal fraction or FF) correlates with test success and interpretation reliability. Some fetal disorders are associated with systematically lower FF, sometimes resulting in noninformative results. Methods We analyzed results from pregnancies tested in a nested case/control study derived from a cohort of 4664 high‐risk pregnancies. Low FF was defined before and after adjusting for maternal weight and gestational age. Results Compared with euploid pregnancies, the median FF was significantly higher in Down syndrome pregnancies (ratio 1.17) and significantly lower in trisomy 18 and triploid pregnancies (ratios 0.71 and 0.19, respectively). Among 2157 pregnancies tested, 13 (0.6%) had FF <3.0% (all noninformative), including three trisomy 18 and three triploidy fetuses. After adjustment, 16 pregnancies (0.7%) had FF <0.3 multiples of the median (six informative), including one trisomy 18 and three triploidy fetuses. Modeled positive predictive values for low and high‐risk populations were 7% and 30%, respectively. Conclusion Among women with noninformative results attributable to low FF, trisomy 18 and/or triploidy risk are sufficiently high to warrant offering additional assessments (e.g. ultrasound). If the testing indication is ultrasound abnormality, amniocentesis and karyotype/microarray should be considered. © 2014 John Wiley & Sons, Ltd.